Enhancing physics hands-on lab through online educational tools - Babayeva, Marina (Scientia in educatione, 2025)
The integration of digital tools into physics education offers new opportunities to enhance student engagement, support differentiated instruction, and facilitate hands-on learning. Despite the growing availability of such tools, educators often face challenges in selecting and implementing platforms that align with pedagogical goals and classroom realities. This study aims to provide a structured overview of online educational tools relevant to secondary-level physics instruction, focusing on their categorization by functionality and potential classroom use. A preliminary review was conducted to identify and classify tools based on core features such as content delivery, assessment, collaboration, and simulation. A pilot study and two educator workshops were used to illustrate practical integration strategies and gather initial feedback from teachers. The findings highlight the value of platform consolidation, the importance of usability and accessibility, and the need for inclusive materials. The categorization framework and illustrative cases offer practical guidance for teachers designing their own lessons and selecting tools purposefully. Future research will explore AI-based solutions tailored to hands-on physics laboratories.